Vasomotor sympathetic outflow in the muscle metaboreflex in low birth weight young adults - Chifamba J; Mbangani B; Chimhete C; Gwaunza L; Allen LA; Chinyanga HM (Dove Medical Press, 2015)
Jephat Chifamba,1 Brilliant Mbangani,1 Casper Chimhete,1 Lenon Gwaunza,1 Larry A Allen,2 Herbert Mapfumo Chinyanga1 1Department of Physiology, College of Health Sciences, University of Zimbabwe, Harare, Zimbabwe; 2Section of Advanced Heart Failure and Transplantation, University of Colorado School of Medicine, Aurora, CO, USA Abstract: A growing body of evidence suggests that low birth weight (LBW) offspring are associated with long-term structural and functional changes in cardiovascular and neuroendocrine systems. We tested the hypothesis that muscle metaboreflex activation produces exaggerated responses in cardiac autonomic tone (represented by heart rate variability ratio) and cutaneous vascular sympathetic tone (represented by plethysmography pulse wave amplitude) in LBW compared to normal birth weight (NBW) young adults. We recruited 23 LBW (18 females and five males) and 23 NBW (14 females and nine males) University of Zimbabwe students with neonatal clinical cards as proof of birth weight at term. Resting electrocardiogram, pulse waves, and blood pressures were recorded. Participants then underwent a static/isometric handgrip exercise until fatigue and a post-exercise circulatory arrest period of 2 minutes. We observed (results mean ± standard deviation) a greater mean increase in heart rate variability ratio from baseline to exercise for LBW compared to NBW individuals (1.015±1.034 versus [vs] 0.119±0.789, respectively; P<0.05). We also observed a greater mean decrease in plethysmography pulse wave amplitude from baseline to exercise (-1.32±1.064 vs -0.735±0.63; P<0.05) and from baseline to post-exercise circulatory arrest (-0.932±0.998 vs -0.389±0.563; P<0.05) for LBW compared to NBW individuals. We conclude that LBW may be associated with an exaggerated sympathetic discharge in response to muscle metaboreflex. Keywords: blood pressure, heart rate variability, plethysmography pulse